2017
DOI: 10.3390/ijms18122675
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nanofunctionalized Gelatin Methacrylate Hydrogels

Abstract: Given the importance of the extracellular medium during tissue formation, it was wise to develop an artificial structure that mimics the extracellular matrix while having improved physico-chemical properties. That is why the choice was focused on gelatin methacryloyl (GelMA), an inexpensive biocompatible hydrogel. Physicochemical and mechanical properties were improved by the incorporation of nanoparticles developed from two innovative fabrication processes: High shear fluid and low frequencies/high frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 39 publications
5
63
0
Order By: Relevance
“…3 A). The results might be attributed to the relative large pore size in lower GelMA proportion of hydrogels, which facilitated the solutions filling into the interconnected pores of hydrogels [ 58 ]. In addition, the swelling ratio of GelMA-bFGF hydrogels decreased by increasing the total polymer concentrations, which was consistent with the observation on pure GelMA hydrogels described in previous study [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 A). The results might be attributed to the relative large pore size in lower GelMA proportion of hydrogels, which facilitated the solutions filling into the interconnected pores of hydrogels [ 58 ]. In addition, the swelling ratio of GelMA-bFGF hydrogels decreased by increasing the total polymer concentrations, which was consistent with the observation on pure GelMA hydrogels described in previous study [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first aim of our study was to identify the optimal composition of a bioink to maintain HepaRG cultivation in a printed 3D construct. Although being of non-human origin, the suitability of alginate [ 19 ] and gelatin [ 16 , 17 , 18 , 32 ] for the fabrication of 3D scaffolds and bioprinting has been well established [ 33 , 34 ]. Our previous results for the 3D printing of lung epithelial cells showed favorable characteristics of blends containing alginate and gelatin in terms of printability, cell viability and preservation of the shape of the generated constructs during culture [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rahali et al functionalized GelMA hydrogels with naturally derived nanoliposomes and reported that the incorporation of nanoliposomes enhanced the mechanical stability of the functionalized GelMA hydrogels; proven by their higher resistance to twist and shear . Similarly, it was also demonstrated that the incorporation of nanoliposomes within alginate/GelMA hydrogels affected the rheological properties of the formed hydrogels, as well as their mechanical properties .…”
Section: Properties Of Soft Nanoparticle–functionalized Hydrogelsmentioning
confidence: 99%